Hubungan Self Efficacy Dengan Pelaksanaan Mobilisasi Dini Pasien Apendektomi Di Ruang Bedah RSUD H. Boejasin Pelaihari - Yohanna Hartatyaningsi; Dyah Trifianingsih; Aulia Rachman; Ermeisi Er Unja (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
One of the nursing interventions in recovery and healing the appendectomy wounds is early mobilization exercises. One of the factors that influence the success of early mobilization is to increase self-efficacy. This research want to determine the correlation of self-efficacy and early mobilization among appendectomy patients in surgery room at H. Boejasin Pelaihari Hospital. The study conducted by utilizing quantitative research with cross sectional approach. There are 20 respondents involved in the study that selected using accidental sampling. The analysis use an spearman rank formula to determine the correlation between two variables. The results showed that the self-efficacy of patients after appendectomy. There are 12 respondents (60%) showed their self-efficacy level in moderate level. 11 respondents (55%) had a good mobilization exercise. Analysis of Spearman Rank correlation found that there was a strong significant relationship between self-efficacy and mobilization among appendectomy patient where the value of p = 0.000.